Study of a problem of functionally graded hollow disk under different thermoelasticity theories - An analysis of phase-lag effects - Kothari, S.; Mukhopadhyay, S. (Elsevier Ltd, 2013)
The present paper is aimed at the investigation of thermo-mechanical interactions inside a functionally graded hollow disk under different thermoelasticity theories in a unified way. The material of the disk is assumed to be graded along its radial direction such that the profiles of the material properties are assumed to follow a volume-fraction based rule with a power law. The inner and outer surfaces of the disk are subjected to different thermal and mechanical boundary conditions. Galerkin type finite element method is used to solve the coupled equations arising out in the present problem in Laplace transform domain. Solution in space-time domain is obtained by employing a numerical inversion method. A detailed analysis highlighting the effects of phase-lags at different times upon the different fields like displacement, temperature, radial stress and hoop stress for different values of the non-homogeneity index is presented by various graphical plots of our numerical results.
Keywords: Functionally graded material; Galerkin finite element method; Thermoelasticity with dual phase-lags; Three phase-lag model; Type III thermoelasticity